Anheuser-Busch InBev and SABMiller : would strategic benefits come easily with Newco - Zidel, David; Townsend, Stephanie Z. (London : SAGE Publications Ltd, 2017)
On 11 November 2015, Carlos Brito, chief executive of global leading beer brewer Anheuser-Busch InBev (AB InBev), presented his final offer of US$105.5 billion (D69.8 or D44 pounds per share), to acquire its rival, SABMiller, which the company accepted. The acquisition process had started in September and just over a month later, on 13 October, SABMiller had accepted the offer in principle, but had certain requirements before it would accept. Such a massive transaction could well present hurdles one being anti-competitive issues. But would this acquisition deliver synergies soon enough for InBev, Brito wondered?
Originally published: Zidel, D., & Townsend, S. (2015). Anheuser-Busch InBev and SABMiller: would strategic benefits come easily with Newco WBS-2016-04. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Anheuser-Busch, Inc; SABMiller (Firm); Consolidation and merger of corporations -- United States; Beer industry -- Mergers -- United States -- History; Brewing industry -- Mergers -- United States -- History